Pelatihan Ketrampilan Merajut Guna Meningkatkan Potensi Ekonomi Kelompok PKK di Kelurahan Margahayu Kota Bekasi - Kumalasari, Ratih; Bastoni (Fakultas Teknik Universitas Bhayangkara Jakarta Raya, 2024)
Community service has been carried out in Margahayu Village, Bekasi City, which was attended by PPK mothers in RT 003/ RW 12 and guided directly by KKN students from the Faculty of Engineering, Bhayangkara University, Jakarta Raya accompanied by Field Supervisors. This community service activity aims to improve the ability of mothers to innovate and improve the economy of residents by becoming entrepreneurs selling their own products. The community service was carried out for one full day, starting with socialization about knitting, knitting practice, training in selling knitted products through e-commerce and evaluation of activities. This community service succeeded in improving the ability and understanding of participants about knitting and increasing enthusiasm in innovating more to create works that have economic value.